Discipline, Infrastructure, Work Environment, and Work Rewards' Influence on Lecturer Performance - Ramanata Disurya; Neta Dian Lestari; Rambat Nur Sasongko; Muhammad Kristiawan (STAI Hubbulwathan Duri, 2022)
This study is to evaluate and analyze the hurdles and problems that a lecturer has in obtaining peak performance by examining the impact of discipline, infrastructure, work environment, and work rewards on lecturer performance. The sample of this study were 32 respondents and this study is quantitative and questionnaire was used to collect the data. We identify or uncover causality to determine the link or impact of discipline, infrastructure, work environment, and job rewards on lecturer performance in statistics are used in this study. The findings revealed that the existence of the Work Reward variable as a control variable had an effect on the variables discipline (X1), infrastructure (X2), work environment (X3) and lecturer performance (Y). Thus, it can be inferred that the variables of discipline, infrastructure, and work environment are not the only factors that influence lecturer performance, because another variable, namely the work reward variable, also has an impact on lecturer performance. Work reward, is one of the variables influencing the rise in discipline, infrastructure, and work environment on lecturer performance. Meanwhile, the statistical results of SPSS 25 show that discipline, infrastructure, work environment, and job rewards all have a substantial impact on professor performance.